From Novice to Seasoned Practitioner: a Qualitative Investigation of Genetic Counselor Professional Development. Issue 4 (9th November 2015) - Zahm, Kimberly Wehner; Veach, Patricia McCarthy; Martyr, Meredith A.; LeRoy, Bonnie S.
Abstract: Research on genetic counselor professional development would characterize typical developmental processes, inform training and supervision, and promote life‐long development opportunities. To date, however no studies have comprehensively examined this phenomenon. The aims of this study were to investigate the nature of professional development for genetic counselors (processes, influences, and outcomes) and whether professional development varies across experience levels. Thirty‐four genetic counselors participated in semi‐structured telephone interviews exploring their perspectives on their professional development. Participants were sampled from three levels of post‐degree genetic counseling experience: novice (0–5 years), experienced (6–14 years), and seasoned (>15 years). Using modified Consensual Qualitative Research and grounded theory methods, themes, domains, and categories were extracted from the data. The themes reflect genetic counselors' evolving perceptions of their professional development and its relationship to: (a) being a clinician, (b) their professional identity, and (c) the field itself. Across experience levels, prevalent influences on professional development were interpersonal (e.g., experiences with patients, genetic counseling colleagues) and involved professional and personal life events. Common developmental experiences included greater confidence and less anxiety over time, being less information‐driven and more emotion‐focused with patients, delivering "bad news" to patients remains challenging, and individuals' professional development experiences parallel genetic counseling's development as a field. With a few noteworthy exceptions, professional development was similar across experience levels. A preliminary model of genetic counselor professional development is proposed suggesting development occurs in a non‐linear fashion throughout the professional lifespan. Each component of the model mutually influences the others, and there are positive and negative avenues of development.